Pengaruh Pengungkapan Enterprise Risk Management (ERM) terhadap Nilai Perusahaan dengan Kinerja Keuangan sebagai Variabel Mediasi - Nadila Putri Yalni; Deviani Deviani (Universitas Negeri Padang, 2026)
This study aims to examine the effect of enterprise risk management disclosure (ERM) and financial performance as mediating variables on firm value. The population in this study are consumer cyclicals companies listed on the Indonesia Stock Exchange (IDX) for the period 2022-2024. The sampling method used is perposive sampling, resulting in a sample of 86 companies. The data analysis method used is multiple linear regression analysis. The results of the of the study indicate that enterprise risk management disclosure (ERM) not effect firm value. Meanwhile, financial performance is unable to mediate the effect of enterprise risk management disclosure (ERM) on firm value.